An investigation on approaches used to teach literature in the ESL classroom: a case study of Sekolah Menengah Kebangsaan Taman Desa Skudai, Johor Bahru - A. Aziz , Marzilah; Syed Nasharudin, Sharifah Nadia (2010)
Literature of English has become part of the KBSM syllabus in Malaysian education system. The mode of delivering the content can be done in various ways. However, not all teachers are aware of the possible best ways of teaching literature. This study was carried out to investigate the approaches used to teach literature in the ESL classroom in Sekolah Menengah Kebangsaan Taman Desa Skudai, Johor Bahru. An investigation was conducted involving 60 form four students which were divided into two groups equally. They were taught literature using two different approaches and given sets of questionnaire to be answered at the end of the lesson. An interview was also done with the teacher to reinforce the findings. The overall findings of the study signify that most of the students prefer a language-based approach lesson more than the integrated approach. This study also reveals that there were weaknesses and strengths found in both approaches. In conclusion, it can be said that the language-based approach is the most preferred approach by the students in this group. However, it depends on how teacher manipulate the situation to suit students’ needs. Finally, it is suggested that teachers need to improve their method and approach of teaching so as to promote an effective teaching environment in literature class.